2021
DOI: 10.1016/j.ijid.2021.02.110
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiological analysis identifies high relapse among individuals with recurring tuberculosis and provides evidence of recent household-related transmission of tuberculosis in Ghana

Abstract: To retrospectively investigate the cause of recurring tuberculosis (rcTB) among participants with pulmonary TB recruited from a prospective population-based study conducted between July 2012 and December 2015. Methods: Mycobacterium tuberculosis complex isolates obtained from rcTB cases were characterized by standard mycobacterial genotyping tools, whole-genome sequencing, and phylogenetic analysis carried out to assess strain relatedness. Results: The majority (58.3%, 21/36) of study participants with rcTB ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…This means that established relapse cases may not actually be relapse events hence we advocate for the use of WGS which is more robust and relatively free from convergence evolution. Using WGS, it was possible to accurately detect relapse from a Ghanaian cohort; this study identified a couple of individuals who were previously infected with drug sensitive strains but later had TB recurrence harboring drug resistant strains (121). This shows the possibility to track such recurring cases and highlights the need to foster genomic epidemiology to aid early detection of drug resistance emergence to provide an effective TB control.…”
Section: Mtbc Surveillance and Transmission In West Africamentioning
confidence: 95%
See 2 more Smart Citations
“…This means that established relapse cases may not actually be relapse events hence we advocate for the use of WGS which is more robust and relatively free from convergence evolution. Using WGS, it was possible to accurately detect relapse from a Ghanaian cohort; this study identified a couple of individuals who were previously infected with drug sensitive strains but later had TB recurrence harboring drug resistant strains (121). This shows the possibility to track such recurring cases and highlights the need to foster genomic epidemiology to aid early detection of drug resistance emergence to provide an effective TB control.…”
Section: Mtbc Surveillance and Transmission In West Africamentioning
confidence: 95%
“…Surveillance activities geared toward understanding MTBC transmission are necessary to complement conventional control efforts to allow the establishment of good preventive strategies, appropriate therapy, and a better understanding of the pathogen biology thereby contributing to the development of future control tools and ultimately helping eliminate TB. These surveillance activities are specifically needed (1) To correctly identify, characterize and track MTBC lineages/strains; (2) To detect risk factors associated with the disease; (3) To understand MTBC person-to-person transmission dynamics, which has been studied extensively in developed countries of North America and Europe as well as other parts of the world and has been useful for identification of outbreaks as well as most at risk groups (33,48,(118)(119)(120) for targeted control activities and; (4) To track TB strains among recurring TB patients and provide indications of the cause of secondary case source (121)(122)(123), for appropriate treatment, evaluation of performance and epidemiology (32,124). To effectively control TB in West Africa, it is therefore paramount to undertake such investigations in a populationbased scale which will contribute to knowledge on factors that enhance spread of the disease in the sub-region.…”
Section: Mtbc Surveillance and Transmission In West Africamentioning
confidence: 99%
See 1 more Smart Citation
“…The NMIMR has collaborated with the National TB control programme (NTP) since 2002 in the development of laboratory manuals, training of laboratory personnel across Ghana on TB microscopy and quality assurance (41,42) and in 2013 assisted the NTP to conduct the first nationwide TB survey (43). Having understood the genotypic distribution of members of the causative organism, Mycobacterium tuberculosis complex (MTBC) (44, 45), novel in Ghana, the Institute has performed populationbased molecular epidemiological studies to identify hotspots of TB transmission (46) detect factors that drive recurrence of the disease (47) as well as identifying other predisposing factors such as ethnicity (48, 49) and diabetes (50). The results have been used by the NTP to direct control measures to help curb the disease burden.…”
Section: Tuberculosismentioning
confidence: 99%